Less Is More: Ludwig Mies Van Der Rohe, Glass Houses And Immigration - Rulli, Daniel (Teaching History: A Journal of Methods, 2007)
When the Armour and Lewis Institutes of Chicago merged in 1940 to form the Illinois Institute of Technology (IIT), the director of architecture, Ludwig Mies van der Rohe, was asked to develop plans and design the buildings for the newly expanded 120-acre campus. Not since Thomas Jefferson’s design of the University of Virginia in 1819 had a university campus been the work of a single architect. This responsibility was accorded to van der Rohe just two years after his entry into the United States and foretold the pivotal impact that his architecture would have on America and the world. Soon after his retirement from IIT in 1958, van der Rohe was awarded Gold Medals by both the Royal Institute of British Architects and the American Association of Architects. Five years later, President Lyndon Johnson presented van der Rohe with the Presidential Medal of Freedom, America’s highest civilian award.